Student Perspectives on Civic Engagement in Strengthening Gender Equality in Higher Education (A Study at UIN Siber Syekh Nurjati Cirebon and Jambi University) - Nurchotimah, Aulia Sholichah Iman; Candra, Alif Aditya; Cahyono, Sigit Pandu; Patrisya, Meysita Intan (Yogyakarta State University, 2024)
This research aims to identify both the similarities and significant differences in student perspectives regarding civic engagement and its role in promoting gender equality in higher education at UIN Siber Syekh Nurjati Cirebon and Jambi University. Additionally, the study aims to understand the implications of these perspectives for advancing gender equality at both institutions. The research uses qualitative methods to explore student views on gender equality and its connection to civic engagement through data collection methods such as interviews, observations, and document analysis. The findings indicate that civic engagement can serve as an effective mechanism for enhancing gender equality in various higher education contexts. Students from both universities express an awareness of their critical roles in addressing gender equality issues, although their approaches differ due to religious and secular influences. These insights can guide universities in developing policies that better cater to student needs and foster gender equality through civic engagement. Moreover, the research suggests that a favourable student perspective on civic engagement related to gender equality may act as a catalyst for transformative change across campuses. Despite differing approaches, civic engagement at both institutions has the potential to raise awareness, shape more inclusive policies, and empower students to become advocates for gender equality within their campuses and communities. These results emphasize the necessity for institutional support and the creation of forums where students can express and explore their views on gender equality.